In vitro assessment of the insoluble phosphatesolubilizing/mineralizing potential of endophytic bacteria from mangrove plants. - MARROIG, L. B. (2023)
The present work evaluated 180 bacteria isolated from Avicennia schaeuriana, Laguncularia racemosa, and Rhizophora mangle from a mangrove area impacted by an oil spill in Bertioga/SP. They were reactivated from the stock in Tryptone Soy Agar and incubated at 28°C for up to 7 days. The ability to solubilize insoluble inorganic [Ca3(PO4)2; AlPO4; FePO4] and organic (hydrated phytic acid sodium salt) phosphate sources were investigated in solid media. All 180 bacteria were inoculated (triplicate) in the following culture media: NBRIP-Ca, NBRIP-Al, NBRIB-Fe, and phytase screening medium.